Product Diversification and Strategy Implementation Public Relations in Setu Babakan - Pradini, Gagih; Awaloedin, Dipa Teruna; Saleh, Muhammad Surya; Andini, Davi Ayu (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Tourism faces the challenge of innovation and diversification to attract a varied audience. This study focuses on the role of Public Relations (PR) in promoting product diversification, particularly in cultural, culinary, and interactive experiences. Setu Babakan, a cultural destination in Jakarta, serves as the case study. The research utilizes qualitative methods, emphasizing observation and interviews, to explore the diversification potential and implementation of PR strategies. The study applies SWOT analysis for comprehensive strategic planning, addressing internal strengths and weaknesses, along with external opportunities and threats.